Retrospective analysis of capillary hemoglobin recovery in nearly 1 200 000 blood donor returns - Pia Niittymäki; Mikko Arvas; Antti Larjo; Pirkko Mattila; Jarkko Ihalainen; Martti Syrjälä; Johanna Castrén; Jukka Partanen (Blood Advances, 2017)
Abstract: Measuring the concentration of capillary hemoglobin (cHb) is a standard procedure before blood donation. To further assess the time period needed for cHb recovery after blood donation and to have a more in-depth understanding of features of recovery, we used data-mining tools in a large, retrospective data pool containing all 1 163 524 donor returns that took place in Finland in 2010 to 2015. The results show that the average recovery times for cHb to return back to the level preceding donation were substantially longer, over 200 days in all age groups, than were the minimum allowed donation intervals. cHb recovery was especially poor in women under the age of 30 who returned to donate soon after the minimum allowed donation interval. It was of interest that frequent donors recovered substantially faster, with the average recovery times of ∼100 days in men and ∼200 days in women, than did infrequent donors, suggesting that there is a subpopulation of donors who can donate frequently without fear of iron deficiency. Return interval in fact explained only 1% of the variation in cHb recovery, which points to unknown, individual features, such as genetic or lifestyle factors, warranting further studies and suggesting that simply extending the allowed donation intervals may not suffice to improve cHb recovery. The study demonstrates that data mining of blood bank records is a powerful tool for depicting features of blood donor population.